The earthquake effect of double storey steel structure due to Aceh Earthquake - Siti Hajar, Sa’adin (2016)
This research refers to the seismic behaviour of double storey steel structure due to Aceh Earthquake. Nowadays, steel structures are widely used all around the world. However, seismic design were not concerned by Civil Engineers in Malaysia almost in all of the building. Recently, few earthquake start occurring in few regions in Malaysia and neighbouring country like Indonesia and Philippines. The tremors occur in this neighbouring country affect the steel structure in Malaysia which the steel structural in Malaysia are not design to resist seismic loading. The objective of this study is to model and analyses the steel structure subjected to different earthquake loads in SAP 2000 program and to determine the best mode shape of free vibration analysis. Besides that, this research also to study the behaviour of double storey steel structure that subjected to different earthquake loading and to determine the performance of double storey steel structure under different earthquake loadings. The earthquake load are analysed accordance to Eurocode 8 and the steel structure are analysed accordance to Eurocode 3. There are four types of analysis that will be carry out which is Free Vibration Analysis, Linear Static Analysis, Response Spectrum Analysis and Time History Analysis. The 12 mode shape with the period and frequency are obtained from Free Vibration Analysis. From Static Analysis, Response Spectrum Analysis and Time History Analysis, the displacement, shear force and bending moment is obtained. The Response Spectrum Analysis provides insight into dynamic behaviour by measuring pseudo-spectral acceleration, velocity, or displacement as a function of structural period for a given time history and level of damping. The percentage of damping used in Malaysia is a damping of 0.05 (5%). Time history analyses the structural response which is computed at a number of subsequent time instants. Time History analysis are performed using the data of earthquake that occur in Aceh in 2004. The software program SAP 2000 is chosen to analyses this steel structure. Several items are studied and analysed by comparing the results generated by the models using a computer program, SAP 2000 in each analysis. However, the simulation of the model of the steel structure is not similar to the condition of the actual structure which is there is no consideration of pile-soil interaction and connection of the steel structure.